Evaluation of the smoking intervention X:IT after the second year: A randomized controlled trial. Issue 8 (December 2019) - Andersen, Anette; Bast, Lotus S.; Due, Pernille; Thygesen, Lau C.
Aims: Review studies on the long-term effects of school-based smoking interventions show mixed results. X:IT was a three-year cluster randomized controlled trial to prevent uptake of smoking among Danish students from age 13 years until age 15 years which previously proved effective in preventing smoking after the first year of intervention. The aim of this paper was to conduct the pre-planned analyses of the effects of the X:IT intervention on smoking after the second year.Methods: We used self-reported questionnaire data from students at baseline, first, second, and third follow-up ( n at second follow-up=3269, response rate=79.4%). Data from third follow-up were not suitable for analysis. Outcome measure: 'current smoking', dichotomised into smoke daily, weekly, monthly or more seldom versus do not smoke. We performed multilevel, logistic regression analyses of available cases and intention-to-treat (ITT) analyses, replacing missing outcome values by multiple imputation.Results: The prevalence of smoking increased from 5.8% at baseline to 17.0% at second follow-up among students at intervention schools, and from 7.6% to 18.7% among students at control schools. Analyses of available cases and ITT analyses did not support X:IT being effective in preventing smoking after the second year of intervention. Conclusions: Although X:IT was effective after the first year of intervention, we were not able to demonstrate any effects after the second year. Implementation of the intervention was lower in the second year compared to the first year which indicates that the missing effect of the intervention at second follow-up is due to lack of implementation.